Graphene cooperates with zinc scale to repair long-acting fastening anticorrosion composite coating and preparation method thereof

CN122917643APending Publication Date: 2026-10-16SICHUAN JIANGYUAN HONGSHENG TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611345795.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-01
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

然而,现有研究多采用将不同功能填料分别加入树脂体系的方式,各组分在涂层中的分布位置和界面结合状态较难控制,容易产生团聚、界面不稳定以及缓蚀组分提前迁移等现象

Benefits of technology

本发明通过对鳞片锌、氧化石墨烯、六方氮化硼和钼酸根缓蚀组分进行有序复合,使各功能组分在复合填料内部形成较稳定的结合关系。首先,采用3-氨丙基三乙氧基硅烷对鳞片锌进行表面处理,有利于氧化石墨烯均匀附着在鳞片锌表面,使鳞片锌的牺牲阳极保护作用与氧化石墨烯的屏障作用能够较好配合,减缓水分、盐分等腐蚀介质向金属基材内部渗透。其次,聚多巴胺能够改善六方氮化硼表面的结合能力,并为Mg-Al层状双氢氧化物的负载提供稳定界面,六方氮化硼本身的片层结构还能够进一步延长腐蚀介质的渗透路径,并减轻紧固过程中摩擦、挤压对涂层造成的局部损伤。钼酸根被预先负载在Mg-Al层状双氢氧化物层间,可减少其在涂层完整状态下过早迁移或与鳞片锌提前接触;当涂层受到划伤、磨损后,腐蚀介质进入损伤区域,可促使钼酸根逐步释放并在局部发挥缓蚀作用,同时与鳞片锌腐蚀过程中形成的含锌组分共同参与保护性沉积的形成,从而减缓腐蚀继续扩展。进一步地,本发明将含钼酸根的复合单元预先设置在氧化石墨烯改性鳞片锌附近,使缓蚀组分释放后能够更快作用于腐蚀区域。因此,本发明能够兼顾涂层完整状态下的长期屏障防护和损伤后的持续缓蚀保护,提高紧固件在长期服役及反复装配条件下的防腐稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application belongs to the technical field of metal anticorrosive coating, and discloses a graphene and flaky zinc synergistic self-repairing long-acting fastening anticorrosive composite coating and a preparation method thereof. The composite coating comprises bisphenol A type epoxy resin, structured composite modified flaky zinc, polyamide curing agent and additives. The structured composite modified flaky zinc is composed of graphene oxide modified flaky zinc and molybdate intercalated Mg-Al layered double hydroxide supported polydopamine modified hexagonal boron nitride. In the preparation, the graphene oxide modified flaky zinc and the molybdate intercalated composite unit are respectively constructed, then liquid phase composite assembly is carried out, and the obtained structured composite modified flaky zinc is added into the pre-dispersed epoxy resin system. Through interface modification, barrier protection, corrosion inhibition component limited release and space synergistic effect, the long-term corrosion resistance, damage corrosion inhibition and fastening use stability of the coating are improved, and the coating is suitable for surface protection of bolts, nuts and other metal fasteners.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of metal anti-corrosion coating technology, specifically relating to a graphene-synergistic flake zinc self-healing long-lasting fastening anti-corrosion composite coating and its preparation method. Background Technology

[0002] Metal fasteners are widely used in machinery, transportation, power facilities, marine engineering, and building structures. During their service life, they are typically exposed to humid, salt spray, industrial media, and temperature-changing environments, making them susceptible to electrochemical corrosion. Bolts and nuts, in particular, are subjected to friction, compression, and localized shearing during assembly and disassembly. If the coating is scratched, worn, or partially damaged, corrosive media can easily penetrate from the defective areas into the substrate, reducing the long-term reliability of the fasteners. Therefore, anti-corrosion coatings that combine high barrier properties, resistance to mechanical damage, and sustained protection after damage have always been an important research direction in this field.

[0003] Currently, zinc-rich epoxy coatings, which provide sacrificial anode protection through zinc particles, are a commonly used technology for fastener corrosion protection. While using flake zinc can extend the penetration path of corrosive media, high-content zinc fillers are prone to uneven dispersion, insufficient interfacial bonding, and degradation of protective capabilities after long-term service. In recent years, two-dimensional materials such as graphene, graphene oxide, and hexagonal boron nitride, due to their layered barrier properties, have been used to improve coating density and corrosion resistance. Simultaneously, layered double hydroxides and other nanocarriers loaded with molybdates and other corrosion-inhibiting components have also been used to impart a certain degree of active corrosion inhibition to coatings. However, existing research often employs the method of adding different functional fillers separately to the resin system. The distribution and interfacial bonding of each component in the coating are difficult to control, easily leading to agglomeration, interfacial instability, and premature migration of corrosion-inhibiting components. Especially after localized damage to the coating, there may be a spatial distance between the release site of the corrosion-inhibiting components and the metal corrosion reaction area, making it difficult to fully exert a sustained protective effect.

[0004] Therefore, how to improve the interfacial bonding and spatial distribution between different functional components while maintaining the cathodic protection of flake zinc and the barrier effect of two-dimensional materials, and taking into account both the long-term protection of the complete coating and the active corrosion inhibition performance of the damaged area, remains a problem that needs to be further solved in the field of long-term anti-corrosion coatings for fasteners. Summary of the Invention

[0005] To address the shortcomings mentioned in the background art, the present invention aims to provide a graphene-synergistic flake zinc self-healing long-lasting fastening and anti-corrosion composite coating and its preparation method. By constructing a structured composite system of graphene oxide-modified flake zinc and molybdate-intercalated Mg-Al layered double hydroxide-supported polydopamine-modified hexagonal boron nitride, the interfacial bonding and spatial distribution of functional components are improved, achieving a synergistic effect of barrier protection, cathodic protection and active corrosion inhibition, thereby improving the long-term anti-corrosion performance of fastener coatings and their continuous protection capability after damage.

[0006] The objective of this invention can be achieved through the following technical solutions: A graphene-synergistic flake zinc self-healing long-lasting fastening and anti-corrosion composite coating, wherein the composite coating is prepared from the following raw materials in parts by weight: 100 parts of bisphenol A type epoxy resin, 220-320 parts of structured composite modified flake zinc, 45-65 parts of polyamide curing agent, 0.5-1.5 parts of dispersant, 0.3-1.0 parts of thixotropic agent, 0.1-0.3 parts of defoamer, and 35-60 parts of organic solvent; The structured composite modified flake zinc includes graphene oxide modified flake zinc and molybdate-intercalated Mg-Al layered double hydroxide-supported polydopamine-modified hexagonal boron nitride loaded on the surface of the graphene oxide modified flake zinc; the graphene oxide modified flake zinc includes flake zinc treated with 3-aminopropyltriethoxysilane and graphene oxide loaded on the surface of the flake zinc; when preparing the structured composite modified flake zinc, the mass ratio of the molybdate-intercalated Mg-Al layered double hydroxide-supported polydopamine-modified hexagonal boron nitride to the graphene oxide modified flake zinc is 5-12:100.

[0007] More preferably, the graphene oxide-modified flake zinc is prepared by the following method: 3-aminopropyltriethoxysilane is pre-hydrolyzed in a mixed medium of ethanol and water, and flake zinc is added for surface treatment to obtain aminosilane-modified flake zinc; graphene oxide is pre-dispersed in a mixed medium of ethanol and water, and then the aminosilane-modified flake zinc is added and stirred to composite, so that the graphene oxide is loaded on the surface of the aminosilane-modified flake zinc, and after separation and drying, the graphene oxide-modified flake zinc is obtained.

[0008] More preferably, the median particle size D50 of the zinc flakes is 10–22 μm, and the mass ratio of the zinc flakes, 3-aminopropyltriethoxysilane, and graphene oxide is 100:(0.5–1.5):(0.3–1.0).

[0009] More preferably, the molybdate-intercalated Mg-Al layered double hydroxide supported polydopamine-modified hexagonal boron nitride is prepared by the following method: hexagonal boron nitride is dispersed in tris(hydroxymethyl)aminomethane buffer solution, and dopamine hydrochloride is added for self-polymerization deposition to obtain polydopamine-modified hexagonal boron nitride; the polydopamine-modified hexagonal boron nitride is dispersed in water, and magnesium nitrate hexahydrate and aluminum nitrate nonahydrate are added for co-precipitation and aging to obtain polydopamine-modified hexagonal boron nitride supported on Mg-Al layered double hydroxides; the obtained polydopamine-modified hexagonal boron nitride supported on Mg-Al layered double hydroxides is dispersed in an aqueous solution of sodium molybdate dihydrate for anion exchange to obtain the molybdate-intercalated Mg-Al layered double hydroxide supported polydopamine-modified hexagonal boron nitride.

[0010] More preferably, the median particle size D50 of the hexagonal boron nitride is 0.5–5 μm, the mass ratio of the hexagonal boron nitride to dopamine hydrochloride is 100:(5–10), the molar ratio of Mg2+ provided by magnesium nitrate hexahydrate to Al3+ provided by aluminum nitrate nonahydrate is 2.0–3.0:1, and the molar ratio of MoO42- provided by sodium molybdate dihydrate to Al3+ used in the preparation of the Mg-Al layered double hydroxide is 0.75–1.50:1.

[0011] More preferably, the bisphenol A type epoxy resin is E51 epoxy resin, the polyamide curing agent is polyamide 650, the dispersant is a solvent-based polymeric wetting and dispersing agent for epoxy coatings, the thixotropic agent is hydrophilic fumed silica, the defoamer is a polysiloxane defoamer, and the organic solvent is composed of xylene and n-butanol.

[0012] A method for preparing a graphene-synergistic zinc flake self-healing long-lasting fastening and anti-corrosion composite coating includes the following steps: S1. After pre-hydrolyzing 3-aminopropyltriethoxysilane, surface-treating the zinc flakes is performed. The resulting aminosilane-modified zinc flakes are then stirred and compounded with pre-dispersed graphene oxide to obtain graphene oxide-modified zinc flakes. S2. Hexagonal boron nitride was surface modified with dopamine hydrochloride. Mg-Al layered double hydroxides were formed on the surface of the obtained polydopamine-modified hexagonal boron nitride by co-precipitation of magnesium nitrate hexahydrate and aluminum nitrate nonahydrate. Anion exchange was then performed using an aqueous solution of sodium molybdate dihydrate to obtain molybdate-intercalated Mg-Al layered double hydroxide-supported polydopamine-modified hexagonal boron nitride. S3. The molybdate-intercalated Mg-Al layered double hydroxide supported polydopamine-modified hexagonal boron nitride is added to the dispersion system of graphene oxide-modified flake zinc and stirred for compounding. After separation, washing and drying, the structured composite modified flake zinc is obtained. S4. Pre-disperse the bisphenol A type epoxy resin, organic solvent, dispersant, thixotropic agent and defoamer, then add the structured composite modified flake zinc and mechanically stir to obtain the coating main agent; before use, add polyamide curing agent to the coating main agent and mix evenly to obtain the graphene synergistic flake zinc self-healing long-lasting fastening and anti-corrosion composite coating.

[0013] More preferably, in step S1, 3-aminopropyltriethoxysilane is pre-hydrolyzed in a mixed medium of ethanol and water, and graphene oxide is ultrasonically dispersed before being stirred and compounded with the aminosilane-modified zinc flakes; the apparent pH of the system when the aminosilane-modified zinc flakes and graphene oxide are stirred and compounded is 6.5-7.5; after the aminosilane-modified zinc flakes are added to the graphene oxide dispersion system, mechanical stirring is used for compounding, and ultrasonic treatment is not performed again.

[0014] More preferably, in step S2, dopamine hydrochloride undergoes self-polymerization deposition in a tris(hydroxymethyl)aminomethane buffer solution with a pH of 8.3–8.7; the co-precipitation of Mg-Al layered double hydroxides is carried out under nitrogen protection, and the pH of the co-precipitation system is 9.3–9.5; when anion exchange is performed using an aqueous solution of sodium molybdate dihydrate, the pH of the exchange system is maintained at 7.5–8.5 under nitrogen protection.

[0015] More preferably, in step S3, the apparent pH of the system during stirring and compounding is 6.5 to 7.5.

[0016] The beneficial effects of this invention are: This invention achieves a stable bonding relationship between various functional components within the composite filler by orderly compounding of flake zinc, graphene oxide, hexagonal boron nitride, and molybdate corrosion inhibitors. First, surface treatment of the flake zinc with 3-aminopropyltriethoxysilane facilitates uniform adhesion of graphene oxide to the zinc surface, allowing for a better synergy between the sacrificial anodic protection of the zinc and the barrier effect of the graphene oxide, thus slowing the penetration of corrosive media such as moisture and salt into the metal substrate. Second, polydopamine improves the bonding ability of the hexagonal boron nitride surface and provides a stable interface for the loading of Mg-Al layered double hydroxides. The layered structure of the hexagonal boron nitride itself further extends the penetration path of corrosive media and reduces localized damage to the coating caused by friction and compression during the fastening process. Molybdate ions are pre-loaded between the Mg-Al layered double hydroxide layers, reducing their premature migration or contact with flake zinc when the coating is intact. When the coating is scratched or worn, the corrosive medium enters the damaged area, promoting the gradual release of molybdate ions and their localized corrosion inhibition. Simultaneously, the molybdate ions, along with zinc-containing components formed during flake zinc corrosion, participate in the formation of protective deposits, thereby slowing further corrosion. Furthermore, this invention pre-positions the molybdate-containing composite units near the graphene oxide-modified flake zinc, allowing the released corrosion inhibitors to act more quickly on the corroded area. Therefore, this invention can simultaneously provide long-term barrier protection when the coating is intact and continuous corrosion inhibition after damage, improving the corrosion resistance of fasteners under long-term service and repeated assembly conditions. Detailed Implementation

[0017] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0018] Unless otherwise specified, all chemical reagents used in the embodiments and preparation examples of this invention are commercially available industrial-grade or analytical-grade raw materials, and all resins and coating additives are commercially available industrial products. Specifically, the purity of the zinc flakes is not less than 98%; the graphene oxide is commercially available graphene oxide powder; 3-aminopropyltriethoxysilane is abbreviated as APTES; hexagonal boron nitride is abbreviated as h-BN; dopamine hydrochloride is a raw material for the preparation of polydopamine; tris(hydroxymethyl)aminomethane is abbreviated as Tris; the magnesium source is magnesium nitrate hexahydrate, the aluminum source is aluminum nitrate nonahydrate, and the molybdate source is sodium molybdate dihydrate. The film-forming resin is E51 bisphenol A type epoxy resin, the curing agent is polyamide 650, the dispersant is a solvent-based polymeric wetting and dispersing agent for epoxy coatings, the thixotropic agent is hydrophilic fumed silica, the defoamer is a polysiloxane defoamer, and the organic solvents are xylene and n-butanol.

[0019] Unless otherwise specified, the ethanol-water mixtures described in the following preparation examples are all obtained by mixing anhydrous ethanol and deionized water at a volume ratio of 70:30; when it is necessary to adjust the acidity or alkalinity of the system, the pH of the aqueous phase system and the apparent pH of the ethanol-water mixture system are adjusted by dilute sodium hydroxide aqueous solution or dilute nitric acid aqueous solution.

[0020] The molybdate-intercalated Mg-Al layered double hydroxide supported polydopamine-modified hexagonal boron nitride (hereinafter referred to as PDA-h-BN@MgAl-LDH-MoO4 composite unit) of this invention is described in this invention. In the Mg-Al layered double hydroxide co-precipitation and molybdate exchange processes, the deionized water used is pre-purged with nitrogen for 30 min to reduce the dissolved CO2 content in the water; both the Mg-Al layered double hydroxide co-precipitation and molybdate exchange processes are carried out under nitrogen protection.

[0021] Preparation Example 1: This preparation example provides a method for preparing structured composite modified flake zinc, including the following steps: S1. Weigh 100 g of zinc flakes with a median particle size D50 of 10 μm, wash twice with anhydrous ethanol, and vacuum dry at 50 °C for 2 h. Mix 475 mL of anhydrous ethanol with 25 mL of deionized water, add 0.50 g of 3-aminopropyltriethoxysilane, and stir at room temperature for 30 min for pre-hydrolysis; then add the pretreated zinc flakes and stir at 25 °C for 60 min. After treatment, filter, wash twice with anhydrous ethanol, and vacuum dry at 50 °C for 6 h to obtain aminosilane-modified zinc flakes. Weigh 0.30 g of graphene oxide and add it to 300 mL of ethanol-water mixture, and ultrasonically disperse for 20 min to obtain a graphene oxide dispersion. Add all of the obtained aminosilane-modified zinc flakes to the graphene oxide dispersion, and adjust the apparent pH of the system to 6.5 with dilute sodium hydroxide aqueous solution if necessary, and mechanically stir at 25 °C for 60 min; no further ultrasonic treatment is performed after adding the aminosilane-modified zinc flakes. After the composite was completed, the sample was filtered, washed twice with an ethanol-water mixture, and dried under vacuum at 50°C for 6 h to obtain graphene oxide-modified flake zinc.

[0022] S2. Prepare 500 mL of Tris buffer solution with a concentration of 10 mmol / L and a pH of 8.3. Add 10.0 g of hexagonal boron nitride with a median particle size D50 of 0.5 μm and sonicate for 20 min. Then add 0.50 g of dopamine hydrochloride and stir at 25 °C for 8 h to allow dopamine to self-polymerize and deposit on the surface of hexagonal boron nitride. Monitor the pH of the system during the reaction and maintain it at 8.3 ± 0.1. After the reaction is complete, filter, wash three times with deionized water, and vacuum dry at 50 °C for 6 h to obtain polydopamine-modified hexagonal boron nitride.

[0023] Weigh 5.13 g of magnesium nitrate hexahydrate and 3.75 g of aluminum nitrate nonahydrate, and dissolve them in 150 mL of deionized water pre-purged with nitrogen for 30 min to obtain a Mg-Al mixed salt solution, wherein the molar ratio of Mg2+ to Al3+ is 2:1. Add all of the obtained polydopamine-modified hexagonal boron nitride to 300 mL of deionized water pre-purged with nitrogen for 30 min, and mechanically stir for 20 min to disperse it. Under nitrogen protection and mechanical stirring, add the Mg-Al mixed salt solution at a uniform rate over 60 min, while simultaneously adding 1 mol / L sodium hydroxide aqueous solution dropwise to maintain the pH of the coprecipitation system at 9.3. After the addition is complete, continue stirring for 1 h, followed by aging at 50 °C for 8 h. After aging, filter and wash three times with pre-removed CO2 deionized water to obtain polydopamine-modified hexagonal boron nitride loaded with Mg-Al layered double hydroxides.

[0024] 1.81 g of sodium molybdate dihydrate was weighed and dissolved in 150 mL of deionized water pre-purged with nitrogen for 30 min. All of the polydopamine-modified hexagonal boron nitride loaded with the Mg-Al layered double hydroxide obtained above was added to the resulting sodium molybdate solution. Anion exchange was performed at 60 °C for 8 h under nitrogen protection, with the pH of the system monitored and maintained between 7.5 and 8.5 during the exchange process. After the exchange was completed, the mixture was filtered, washed three times with deionized water, and vacuum dried at 50 °C for 6 h to obtain the PDA-h-BN@MgAl-LDH-MoO4 composite unit; wherein the molar ratio of MoO42- to Al3+ used in the preparation of the Mg-Al layered double hydroxide was 0.75:1.

[0025] S3. Weigh 100 g of the graphene oxide-modified zinc flakes obtained in step S1 and add it to 500 mL of ethanol-water mixture. Stir mechanically for 15 min to form a graphene oxide-modified zinc flake suspension system. Separately weigh 5.0 g of the PDA-h-BN@MgAl-LDH-MoO4 composite unit obtained in step S2 and add it to 100 mL of ethanol-water mixture. Stir mechanically for 15 min for pre-dispersion. Under continuous mechanical stirring, slowly add the obtained composite unit dispersion to the graphene oxide-modified zinc flake suspension system over 15 min, adjust the apparent pH of the system to 6.5, and continue mechanical stirring at 25℃ for 60 min after the addition is complete.

[0026] After the composite was completed, it was filtered, washed twice with an ethanol-water mixture, and dried under vacuum at 50°C for 6 h to obtain structured composite modified flake zinc; wherein the mass ratio of PDA-h-BN@MgAl-LDH-MoO4 composite unit to graphene oxide modified flake zinc was 5:100.

[0027] Preparation Example 2: This preparation example provides another method for preparing structured composite modified flake zinc, specifically including the following steps: S1. Take 100 g of flake zinc with a median particle size D50 of 22 μm, wash twice with anhydrous ethanol, and then vacuum dry at 60 °C for 2 h. Add 1.50 g of 3-aminopropyltriethoxysilane to a pre-hydrolysis system consisting of 475 mL of anhydrous ethanol and 25 mL of deionized water, and stir at room temperature for 30 min; then add all the pretreated flake zinc, and stir at 30 °C for 90 min. After the reaction is complete, filter, wash twice with anhydrous ethanol, and vacuum dry at 60 °C for 6 h to obtain aminosilane-modified flake zinc.

[0028] Separately, 1.00 g of graphene oxide was added to 300 mL of ethanol-water mixture and ultrasonically dispersed for 30 min. After ultrasonication, the above-mentioned aminosilane-modified flake zinc was added, and the apparent pH of the system was adjusted to 7.5. The mixture was mechanically stirred at 30 °C for 120 min, and no further ultrasonic treatment was performed during the composite process. The obtained solid was filtered, washed twice with ethanol-water mixture, and vacuum dried at 60 °C for 6 h to obtain graphene oxide-modified flake zinc.

[0029] S2. 500 mL of Tris buffer (10 mmol / L, pH 8.7) was mixed with 10.0 g of hexagonal boron nitride (median particle size D50 5 μm) and ultrasonically dispersed for 30 min. Then, 1.00 g of dopamine hydrochloride was added, and the mixture was stirred continuously at 30 °C and 300 r / min for 12 h, maintaining the pH at 8.7 ± 0.1 during the reaction. After the reaction was complete, solid-liquid separation was performed, followed by washing three times with deionized water and vacuum drying at 60 °C for 6 h to obtain polydopamine-modified hexagonal boron nitride.

[0030] 7.69 g of magnesium nitrate hexahydrate and 3.75 g of aluminum nitrate nonahydrate were dissolved together in 150 mL of deionized water pre-purged with nitrogen for 30 min to prepare a Mg-Al mixed salt solution, wherein the molar ratio of Mg2+ to Al3+ was 3:1. The resulting polydopamine-modified hexagonal boron nitride was then completely added to 300 mL of pre-removed CO2 deionized water and mechanically stirred for 20 min to redisperse it. Under nitrogen protection, the Mg-Al mixed salt solution was uniformly added over 60 min, while simultaneously adding 1 mol / L sodium hydroxide aqueous solution dropwise to maintain the pH of the coprecipitation system at 9.5. After the mixed salt was completely added, stirring continued for 1 h, followed by aging at 60 °C for 10 h. The aged product was filtered and washed three times with pre-removed CO2 deionized water to obtain polydopamine-modified hexagonal boron nitride loaded with Mg-Al layered double hydroxides.

[0031] 3.63 g of sodium molybdate dihydrate was dissolved in 150 mL of deionized water pre-purged with nitrogen for 30 min. The resulting solid was then transferred entirely into the sodium molybdate solution. Anion exchange was performed under nitrogen protection at 60 °C for 12 h, with the pH of the exchange system maintained between 7.5 and 8.5. After the exchange was completed, the mixture was filtered, washed three times with deionized water, and vacuum dried at 60 °C for 6 h to obtain the PDA-h-BN@MgAl-LDH-MoO4 composite unit. The molar ratio of MoO42- to Al³⁺ used in the preparation of Mg-Al layered double hydroxides was 1.50:1.

[0032] S3. Add 100 g of the graphene oxide-modified flake zinc obtained in step S1 to 500 mL of ethanol-water mixture and mechanically stir for 20 min to form a suspension. Separately, take 12.0 g of the PDA-h-BN@MgAl-LDH-MoO4 composite unit obtained in step S2 and mechanically pre-disperse it in 100 mL of ethanol-water mixture for 20 min. While maintaining continuous stirring of the graphene oxide-modified flake zinc suspension, gradually add the above composite unit dispersion over 20 min, adjusting the apparent pH of the system to 7.5. After the addition is complete, continue mechanical stirring at 30℃ for 90 min. After assembly, filter, wash twice with ethanol-water mixture, and vacuum dry at 60℃ for 6 h to obtain structured composite modified flake zinc; the mass ratio of PDA-h-BN@MgAl-LDH-MoO4 composite unit to graphene oxide-modified flake zinc is 12:100.

[0033] Preparation Example 3: This preparation example provides a method for preparing structured composite modified flake zinc, the specific steps of which are as follows: S1. Weigh 100 g of flake zinc with a median particle size D50 of 16 μm, wash twice with anhydrous ethanol, and vacuum dry at 55 °C for 2 h for later use. Add 1.00 g of 3-aminopropyltriethoxysilane to a mixture of 475 mL of anhydrous ethanol and 25 mL of deionized water, and stir at room temperature for 30 min for pre-hydrolysis; add the pretreated flake zinc, and continue stirring at 25 °C for 75 min. After filtration, wash twice with anhydrous ethanol, and vacuum dry at 55 °C for 6 h to obtain aminosilane-modified flake zinc.

[0034] 0.65 g of graphene oxide was weighed and added to 300 mL of ethanol-water mixture. After ultrasonic dispersion for 25 min, all of the aminosilane-modified flake zinc was added to the mixture. The apparent pH of the system was adjusted to 7.0, and the mixture was mechanically stirred at 25 °C for 90 min. No further ultrasonic treatment was performed after the addition of the flake zinc. The reaction system was filtered, washed twice with ethanol-water mixture, and vacuum dried at 55 °C for 6 h to obtain graphene oxide-modified flake zinc.

[0035] S2. Prepare 500 mL of Tris buffer solution with a concentration of 10 mmol / L and a pH of 8.5. Add 10.0 g of hexagonal boron nitride with a median particle size D50 of 2.5 μm to the buffer solution and sonicate for 25 min. Then add 0.75 g of dopamine hydrochloride. The resulting system is stirred continuously at 25 °C for 10 h, and the pH is maintained at 8.5 ± 0.1 during the reaction. After the reaction is complete, filter the solution, wash three times with deionized water, and dry under vacuum at 55 °C for 6 h to obtain polydopamine-modified hexagonal boron nitride.

[0036] 6.41 g of magnesium nitrate hexahydrate and 3.75 g of aluminum nitrate nonahydrate were dissolved in 150 mL of deionized water pre-purged with nitrogen for 30 min to prepare a Mg-Al mixed salt solution; the molar ratio of Mg2+ to Al3+ was 2.5:1. All of the above polydopamine-modified hexagonal boron nitride was added to 300 mL of pre-removed CO2 deionized water, and mechanically stirred for 20 min to ensure thorough dispersion. While maintaining nitrogen protection and mechanical stirring, the Mg-Al mixed salt solution was added over 60 min, while simultaneously adding 1 mol / L sodium hydroxide aqueous solution dropwise to maintain the pH of the coprecipitation system at 9.4–9.5. After the addition was complete, stirring was continued for 1 h, and the mixture was aged at 60 °C for 10 h. The aged solid was filtered and washed three times with pre-removed CO2 deionized water to obtain polydopamine-modified hexagonal boron nitride loaded with Mg-Al layered double hydroxides.

[0037] 2.72 g of sodium molybdate dihydrate was weighed and dissolved in 150 mL of deionized water pre-purged with nitrogen for 30 min. All of the solid was added to the resulting sodium molybdate solution, and anion exchange was performed under nitrogen protection at 60 °C for 10 h with stirring, maintaining the pH of the exchange system between 7.5 and 8.5. After anion exchange, the mixture was filtered, washed three times with deionized water, and vacuum dried at 55 °C for 6 h to obtain the PDA-h-BN@MgAl-LDH-MoO4 composite unit. The molar ratio of MoO42- to A3+ used in the preparation of the Mg-Al layered double hydroxide was 1.125:1.

[0038] S3. Weigh 100 g of the graphene oxide-modified zinc flakes obtained in step S1 and add it to 500 mL of ethanol-water mixture. Stir mechanically for 20 min to form a graphene oxide-modified zinc flake suspension system. Separately weigh 8.5 g of the PDA-h-BN@MgAl-LDH-MoO4 composite unit obtained in step S2 and add it to 100 mL of ethanol-water mixture. Stir mechanically for 20 min for pre-dispersion. Keep the graphene oxide-modified zinc flake suspension system under continuous stirring. Slowly add the obtained PDA-h-BN@MgAl-LDH-MoO4 composite unit dispersion over 20 min, and adjust the apparent pH of the system to 7.0. After the addition is complete, continue mechanical stirring at 25℃ for 75 min.

[0039] After the composite was completed, it was filtered, washed twice with an ethanol-water mixture, and vacuum dried at 55℃ for 6 h to obtain structured composite modified flake zinc; wherein, the mass ratio of PDA-h-BN@MgAl-LDH-MoO4 composite unit to graphene oxide modified flake zinc was 8.5:100.

[0040] Example 1: This example provides a graphene-synergistic flake zinc self-healing long-lasting fastening and anti-corrosion composite coating, prepared from the following raw materials in parts by weight: 100 parts of E51 bisphenol A type epoxy resin, 220 parts of the structured composite modified flake zinc obtained in Preparation Example 1, 45 parts of polyamide 650 curing agent, 0.5 parts of polymer-type wetting and dispersing agent, 0.3 parts of hydrophilic fumed silica, 0.1 parts of polysiloxane defoamer, and 35 parts of organic solvent; the organic solvent consists of 26 parts of xylene and 9 parts of n-butanol.

[0041] The specific preparation method is as follows: Add E51 bisphenol A epoxy resin to a mixing container, then add xylene, n-butanol, polymeric wetting and dispersing agent, hydrophilic fumed silica and polysiloxane defoamer. Pre-disperse at 800 r / min for 10 min to ensure uniform mixing of resin, solvent and additives, and obtain a resin pre-dispersion system.

[0042] The stirring speed was then reduced to 200 r / min, and the structured composite modified flake zinc obtained in Preparation Example 1 was added in batches to the resin pre-dispersion system, with continuous mechanical stirring during the addition process. After all the material was added, mechanical stirring was continued at 200 r / min for 20 min to ensure that the structured composite modified flake zinc was uniformly dispersed in the resin system, thus obtaining the coating main agent. After the structured composite modified flake zinc was added, only mechanical stirring was used; high-speed dispersion, sand milling, bead milling, or ultrasonic treatment was not performed.

[0043] The obtained coating base and polyamide 650 curing agent were sealed and stored separately. Before use, the polyamide 650 curing agent was added to the coating base according to the above ratio, and mechanically stirred at 300 r / min for 5 min until uniform, to obtain a graphene-synergistic flake zinc self-healing long-lasting fastening and anti-corrosion composite coating.

[0044] Example 2: This example provides a graphene-synergistic flake zinc self-healing long-lasting fastening and anti-corrosion composite coating, prepared from the following raw materials in parts by weight: 100 parts of E51 bisphenol A type epoxy resin, 320 parts of the structured composite modified flake zinc obtained in Preparation Example 2, 65 parts of polyamide 650 curing agent, 1.5 parts of polymer-type wetting and dispersing agent, 1.0 part of hydrophilic fumed silica, 0.3 parts of polysiloxane defoamer, and 60 parts of organic solvent; wherein, the organic solvent consists of 45 parts of xylene and 15 parts of n-butanol.

[0045] During preparation, E51 bisphenol A type epoxy resin, xylene and n-butanol were first added to a mixing container and stirred. Then, polymeric wetting and dispersing agent, hydrophilic fumed silica and polysiloxane defoamer were added in sequence and pre-dispersed at 1200 r / min for 20 min to obtain a uniform resin pre-dispersion system.

[0046] After pre-dispersion, the rotation speed was reduced to 400 r / min, and the structured composite modified flake zinc obtained in Preparation Example 2 was gradually added while maintaining continuous mechanical stirring. After all the zinc was added, mechanical stirring was continued at 400 r / min for 40 min to ensure that the structured composite modified flake zinc was uniformly distributed in the epoxy resin system, thus obtaining the coating main agent. After the addition of the structured composite modified flake zinc, the system was no longer subjected to high-speed dispersion, sand milling, bead milling, or ultrasonic treatment.

[0047] The obtained coating base and polyamide 650 curing agent were sealed and stored separately. Before application, the polyamide 650 curing agent was added to the coating base according to the above formula, and the mixture was mechanically stirred at 300 r / min for 5 min until the system was homogeneous, thus obtaining the graphene-synergistic flake zinc self-healing long-lasting fastening and anti-corrosion composite coating of this embodiment.

[0048] Example 3: This example provides a graphene-synergistic flake zinc self-healing long-lasting fastening and anti-corrosion composite coating, prepared from the following raw materials in parts by weight: 100 parts of E51 bisphenol A type epoxy resin, 270 parts of the structured composite modified flake zinc obtained in Preparation Example 3, 55 parts of polyamide 650 curing agent, 1.0 part of polymer-type wetting and dispersing agent, 0.65 parts of hydrophilic fumed silica, 0.2 parts of polysiloxane defoamer, and 48 parts of organic solvent; the organic solvent includes 36 parts of xylene and 12 parts of n-butanol.

[0049] E51 bisphenol A epoxy resin was mixed with xylene and n-butanol, and polymeric wetting and dispersing agent, hydrophilic fumed silica and polysiloxane defoamer were added. The mixture was mechanically stirred at 1000 r / min for 15 min to fully disperse the components and form a resin pre-dispersion system.

[0050] The stirring speed was adjusted to 300 r / min, and the structured composite modified flake zinc obtained in Preparation Example 3 was added in batches while maintaining mechanical stirring during the addition process. After all the materials were added, mechanical stirring was continued at 300 r / min for 30 min to ensure that the structured composite modified flake zinc was uniformly dispersed in the resin system, thus obtaining the coating main agent. After the structured composite modified flake zinc was added, it was dispersed only by the above-mentioned mechanical stirring method, without high-speed dispersion, sand milling, bead milling, or ultrasonic treatment.

[0051] The obtained coating base and polyamide 650 curing agent are sealed and stored separately. Before use, the polyamide 650 curing agent is added to the coating base according to the above ratio, and mechanically stirred at 300 r / min for 5 min until uniform, thus obtaining the graphene synergistic flake zinc self-healing long-lasting fastening and anti-corrosion composite coating of this embodiment.

[0052] Comparative Example 1: The difference between this comparative example and Example 3 is that, instead of preparing structured composite modified flake zinc, aminosilane modified flake zinc, graphene oxide and PDA-h-BN@MgAl-LDH-MoO4 composite units are added to the coating system for mixing and dispersion.

[0053] Among them, the aminosilane-modified flake zinc was prepared according to the method of treating flake zinc with 3-aminopropyltriethoxysilane in step S1 of preparation example 3, but after the treatment, it was no longer interfacially composited with graphene oxide; the preparation method of the PDA-h-BN@MgAl-LDH-MoO4 composite unit was the same as that in step S2 of preparation example 3.

[0054] Based on the feeding relationship of each functional component in Preparation Example 3, 247.37 parts of aminosilane modified flake zinc, 1.61 parts of graphene oxide, and 21.02 parts of PDA-h-BN@MgAl-LDH-MoO4 composite unit were weighed out, totaling 270 parts, as the mixed functional filler of this comparative example.

[0055] 100 parts of E51 bisphenol A epoxy resin, 36 parts of xylene, and 12 parts of n-butanol were added to a mixing container. Then, 1.0 part of polymeric wetting and dispersing agent, 0.65 parts of hydrophilic fumed silica, and 0.2 parts of polysiloxane defoamer were added. The mixture was mechanically stirred at 1000 r / min for 15 min to obtain a resin pre-dispersion system.

[0056] The stirring speed was then adjusted to 300 r / min, and the above-mentioned aminosilane-modified flake zinc, graphene oxide, and PDA-h-BN@MgAl-LDH-MoO4 composite unit were added sequentially, maintaining mechanical stirring during the addition process. After all the materials were added, stirring was continued at 300 r / min for 30 min to disperse the functional components in the resin system, thus obtaining the coating main agent. No further high-speed dispersion, sand milling, bead milling, or ultrasonic treatment was performed on the functional components after addition.

[0057] The obtained coating base and polyamide 650 curing agent were sealed and stored separately. Before use, 55 parts of polyamide 650 curing agent were added and mechanically stirred at 300 r / min for 5 min until uniform, to obtain the composite coating of Comparative Example 1.

[0058] Comparative Example 2: In the preparation of graphene oxide-modified flake zinc in this comparative example, 3-aminopropyltriethoxysilane was not used to treat the surface of the flake zinc, but graphene oxide was directly compounded with the flake zinc.

[0059] Specifically, 100 g of zinc flakes with a median particle size D50 of 16 μm were weighed, washed twice with anhydrous ethanol, and dried under vacuum at 55°C for 2 h.

[0060] 0.65 g of graphene oxide was weighed and added to 300 mL of ethanol-water mixture, and ultrasonically dispersed for 25 min. Then, all the pretreated zinc flakes were added to the graphene oxide dispersion, the apparent pH of the system was adjusted to 7.0, and the mixture was mechanically stirred at 25 °C for 90 min. No further ultrasonic treatment was performed after adding the zinc flakes. After composite formation, the mixture was filtered, washed twice with ethanol-water mixture, and vacuum dried at 55 °C for 6 h to obtain graphene oxide-modified zinc flakes without APTES interface treatment.

[0061] The preparation method of the PDA-h-BN@MgAl-LDH-MoO4 composite unit is the same as step S2 in Preparation Example 3.

[0062] 100 g of the graphene oxide-modified zinc flakes without APTES interface treatment was weighed and added to 500 mL of ethanol-water mixture, and mechanically stirred for 20 min to form a suspension. Separately, 8.5 g of the PDA-h-BN@MgAl-LDH-MoO4 composite unit was weighed and added to 100 mL of ethanol-water mixture, and mechanically stirred for 20 min for pre-dispersion. Under continuous mechanical stirring, the resulting composite unit dispersion was slowly added to the graphene oxide-modified zinc flake suspension over 20 min, adjusting the apparent pH of the system to 7.0. After the addition was complete, mechanical stirring was continued at 25℃ for 75 min.

[0063] After composite processing, the sample was filtered, washed twice with an ethanol-water mixture, and vacuum dried at 55°C for 6 h to obtain the composite modified flake zinc of Comparative Example 2. The mass ratio of the PDA-h-BN@MgAl-LDH-MoO4 composite unit to the untreated graphene oxide-modified flake zinc was 8.5:100.

[0064] The coating was prepared using 270 parts of the above-mentioned composite modified flake zinc. The composition and amount of E51 bisphenol A epoxy resin, polyamide 650 curing agent, polymer wetting and dispersing agent, hydrophilic fumed silica, polysiloxane defoamer and organic solvent were the same as in Example 3. The coating preparation method was also the same as in Example 3, and the composite coating of Comparative Example 2 was obtained.

[0065] Comparative Example 3: The difference between this comparative example and Example 3 is that after loading Mg-Al layered double hydroxides onto the surface of PDA-h-BN, molybdate anion exchange is not performed, but sodium molybdate dihydrate is added to the coating system as a free corrosion inhibitor.

[0066] Specifically, the PDA-h-BN@MgAl-LDH composite unit was prepared according to the steps before the molybdate anion exchange in step S2 of Preparation Example 3. After aging and washing of the Mg-Al layered double hydroxide, no further molybdate exchange was performed. The product was then vacuum dried at 55°C for 6 h to obtain the PDA-h-BN@MgAl-LDH composite unit.

[0067] Graphene oxide-modified flake zinc was prepared according to the method in step S1 of Preparation Example 3, and assembled with PDA-h-BN@MgAl-LDH composite units according to the feeding ratio and composite conditions in step S3 of Preparation Example 3 to obtain structured composite modified flake zinc without molybdate intercalation.

[0068] The coating was prepared using 270 parts of the above-mentioned structured composite modified flake zinc. The composition, dosage and preparation conditions of the remaining raw materials were the same as those in Example 3. The difference was that sodium molybdate dihydrate was added in the resin pre-dispersion stage. The amount of sodium molybdate dihydrate added was calculated according to the theoretical feeding ratio of sodium molybdate dihydrate to PDA-h-BN@MgAl-LDH-MoO4 composite unit in Preparation Example 3, so as to obtain the composite coating of Comparative Example 3.

[0069] Comparative Example 4: The difference between this comparative example and Example 3 is that the graphene oxide modified flake zinc and the PDA-h-BN@MgAl-LDH-MoO4 composite unit were prepared and liquid-phase treated separately, but the two were not contacted and pre-assembled before entering the coating system.

[0070] Specifically, the graphene oxide-modified flake zinc was prepared according to the method in step S1 of Preparation Example 3, and the PDA-h-BN@MgAl-LDH-MoO4 composite unit was prepared according to the method in step S2 of Preparation Example 3.

[0071] Weigh 100 g of graphene oxide-modified zinc flakes and add them to 500 mL of ethanol-water mixture. Stir mechanically for 20 min, adjust the apparent pH of the system to 7.0, and continue stirring mechanically at 25 °C for 75 min. After the treatment, filter, wash twice with ethanol-water mixture, and vacuum dry at 55 °C for 6 h.

[0072] Another 8.5 g of PDA-h-BN@MgAl-LDH-MoO4 composite unit was added to 100 mL of ethanol-water mixture and mechanically stirred for 20 min. The apparent pH of the system was adjusted to 7.0 and mechanically stirred at 25 °C for another 75 min. After the treatment, the mixture was filtered, washed twice with ethanol-water mixture, and vacuum dried at 55 °C for 6 h.

[0073] The two materials mentioned above are always processed separately during the liquid phase treatment process, without coming into contact with each other or being assembled together.

[0074] The PDA-h-BN@MgAl-LDH-MoO4 composite unit and graphene oxide-modified flake zinc were converted at a mass ratio of 8.5:100, and the total amount of the two functional materials was 270 parts. These were added to the resin pre-dispersion system described in Example 3. After complete addition, the mixture was mechanically stirred at 300 r / min for 30 min to obtain the coating main agent. No high-speed dispersion, sand milling, bead milling, or ultrasonic treatment was performed on the two functional materials after addition.

[0075] The composition, dosage, and curing agent addition method of the remaining raw materials in the coating are the same as those in Example 3, resulting in the composite coating of Comparative Example 4.

[0076] Performance testing To verify the effects of the structured composite modified flake zinc of the present invention on the long-term anti-corrosion performance, active corrosion inhibition performance after damage, and protective stability after fastening, the composite coatings obtained in Examples 1-3 and Comparative Examples 1-4 were used as test samples for performance testing.

[0077] The flat plate specimens were made of Q235 carbon steel plate, with dimensions of 150 mm × 75 mm × 2 mm. After sandblasting to remove rust and cleaning, each group of coatings was applied. After coating, the plates were cured for 7 days at 25±2℃ and 50±5% relative humidity, with the dry film thickness controlled at 70±5 μm. Except for the corrosion resistance retention performance test after repeated tightening, three parallel specimens were set for each group of all other tests; for the corrosion resistance retention performance test after repeated tightening, five sets of parallel specimens were set for each group, and the test results were taken as the average value.

[0078] 1. Electrochemical impedance spectroscopy test of the complete coating Electrochemical impedance spectroscopy (EIS) was performed according to ISO 16773-2:2016. The cured coated steel plate was used as the working electrode, with a platinum electrode as the auxiliary electrode and a saturated calomel electrode as the reference electrode. The effective exposed area of ​​the sample was 10 cm², the test medium was a 3.5% (w / w) NaCl aqueous solution, and the test temperature was 25 ± 2 °C.

[0079] The samples were soaked for 1 day, 7 days, 14 days, and 28 days, respectively. Before each test, the samples were stabilized at an open circuit potential for 30 minutes. The AC disturbance amplitude was 10 mV, and the test frequency range was 100 kHz to 0.01 Hz. The low-frequency impedance modulus at 0.01 Hz after area normalization was recorded and expressed as log10(|Z|0.01Hz / (Ω·cm2)). The results are shown in Table 1 below.

[0080] Table 1. Electrochemical impedance spectroscopy results of the complete coatings in the examples and comparative examples.

[0081] Note: All values ​​in the table are log10(|Z|0.01Hz / (Ω·cm2)).

[0082] The test results show that Examples 1-3 maintained high low-frequency impedance after 28 days of immersion. Example 2 showed a higher initial impedance, indicating good electrochemical protection performance in the early stages of immersion. Example 3 exhibited better impedance retention after long-term immersion, suggesting that appropriate amounts of structured composite modified flake zinc are more beneficial for maintaining the long-term protective stability of the coating. Comparative Example 1 showed the most significant impedance decrease after direct mixing of the functional components; Comparative Example 2, without APTES interface treatment, also showed a significant long-term impedance decrease, indicating that structured construction and flake zinc interface modification are beneficial for improving the long-term corrosion resistance of the coating.

[0083] 2. Electrochemical impedance spectroscopy test after artificial scratching Electrochemical impedance spectroscopy (EIS) tests were performed according to ISO 16773-2:2016. A straight scratch, 10 mm long and approximately 0.5 mm wide, penetrating the coating and reaching the metal substrate, was created in the center of the effective test area of ​​the cured coating. All scratches were of consistent size. Immediately after scratching, the sample was immersed in a 3.5% (w / w) NaCl aqueous solution. Using the same three-electrode system as the complete coating, the test result after 30 min of immersion was recorded as 0 h. Subsequent tests were conducted at 24 h, 72 h, and 168 h. The AC perturbation amplitude was 10 mV, and the test frequency range was 100 kHz to 0.01 Hz. The low-frequency impedance modulus at 0.01 Hz, normalized to the effective test area, was recorded and expressed as log10(|Z|0.01Hz / (Ω·cm²)).

[0084] The results are shown in Table 2 below.

[0085] Table 2. Electrochemical impedance spectroscopy results after artificial scratching in the examples and comparative examples.

[0086] Note: All values ​​in the table are log10(|Z|0.01Hz / (Ω·cm2)).

[0087] The results show that the low-frequency impedance of Examples 1-3 gradually increased within 24-72 hours after artificial scratching. Although it decreased slightly at 168 hours, it was still significantly higher than the initial value, indicating that the damaged area formed a certain degree of sustained protection. Among them, Example 3 reached 5.18 and 5.10 at 72 hours and 168 hours, respectively, demonstrating good post-damage protection retention capability.

[0088] Comparative Example 3, using free molybdate, achieved an impedance of 4.88 after 24 hours, indicating that free molybdate ions could quickly exert an initial corrosion inhibition effect, but subsequently decreased gradually, reaching only 4.48 after 168 hours. In contrast, Example 3 maintained an impedance of 5.10, suggesting that confining molybdate ions within a Mg-Al layered double hydroxide is beneficial for prolonging the corrosion inhibition effect. Comparative Example 4 retained both types of functional units but eliminated pre-composite assembly, resulting in a significantly lower later impedance than Example 3, indicating that pre-spatial assembly between the two types of functional units is beneficial for sustained protection after damage.

[0089] 3. Artificial scratch neutral salt spray corrosion propagation test Salt spray exposure was conducted under neutral salt spray conditions as specified in GB / T 10125-2021. The corrosion spread around the scratch was evaluated in accordance with ISO 4628-8:2012, and the average corrosion spread width of the scratch was determined according to the following method.

[0090] A straight scratch, 50 mm long and approximately 0.5 mm wide, extending to the metal substrate, was made in the center of the cured coating test panel. A salt spray was generated using an approximately 5% (w / w) NaCl aqueous solution, at a test temperature of 35 ± 2 °C, with a salt solution pH of 6.5–7.2, and the exposure was continuous for 720 h.

[0091] After the test, the sample was removed, rinsed with deionized water and dried. Loose corrosion products and lost coating around the scratches were removed using a standardized method. Ten equally spaced locations were selected along the length of the scratch, and the distance from the original scratch edge to the corrosion extension boundary on both sides of the scratch was measured. The average corrosion extension width was calculated.

[0092] The results are shown in Table 3 below.

[0093] Table 3. Results of Neutral Salt Spray Corrosion Propagation under Artificial Scratches in Examples and Comparative Cases

[0094] As shown in Table 3, the average corrosion spread width of the scratches in Examples 1-3 after 720 h of neutral salt spray testing was significantly smaller than that in the comparative examples, with Example 3 showing the lowest width at only 0.58 mm. This indicates that the coating of the present invention can effectively inhibit corrosion spread along the coating / substrate interface even after localized damage. Comparative Example 1, which used direct mixing of functional components, showed the most significant corrosion spread; Comparative Example 3, which used free molybdate, had insufficient long-term protection; and Comparative Example 4, which did not undergo pre-assembly of functional units, still showed higher corrosion spread than the examples, indicating that molybdate confinement and spatial assembly are beneficial for improving the sustained corrosion protection performance after damage.

[0095] 4. Corrosion resistance retention test after repeated tightening Repeated tightening was performed using the simulated tightening conditions set by this invention. The tightening load was applied according to the torque / clamping force test principles of ISO 16047:2005 and ISO 16047:2005 / Amd 1:2012, and the axial clamping force of each group of samples was uniformly set to 30±1 kN. Subsequent salt spray exposure was conducted according to the neutral salt spray conditions specified in GB / T 10125-2021.

[0096] M12×1.75 carbon steel bolts and matching nuts of performance grade 8.8 were selected. After the same surface pretreatment, the coatings obtained in Examples 1-3 and Comparative Examples 1-4 were applied respectively, and cured at 25±2℃ for 7 days. The dry film thickness in the threaded working area was controlled at 30±5 μm, and it was ensured that the coated bolts and nuts could be screwed on normally. Five sets of samples were set up for each group.

[0097] The bolts, nuts, and steel clamps form a fastening assembly without additional lubricant. A fastening test device capable of detecting axial clamping force is used. The sample is tightened to 30±1 kN, held for 30 seconds, and then completely released. This is recorded as one fastening cycle, and five cycles are performed consecutively.

[0098] After the cycle is completed, a fixed observation area is selected in the effective meshing area, and surface images are acquired at the same magnification. The proportion of the area still covered by the continuous coating to the original coating area is calculated by image analysis to obtain the coating integrity rate.

[0099] The samples were then exposed to neutral salt spray for 240 hours. After the test, the samples were cleaned and dried. The proportion of the area with red rust and obvious corrosion products to the total area of ​​the observation area was calculated in the same observation area to obtain the red rust area ratio.

[0100] The results are shown in Table 4 below.

[0101] Table 4. Results of corrosion resistance retention after repeated tightening in the examples and comparative examples.

[0102] As shown in Table 4, the integrity rate of the coatings in Examples 1 to 3 after 5 repeated tightenings was higher than 84%, and the red rust area after further salt spray exposure for 240 h was only 3.8 to 5.8%, indicating that the coatings of the present invention still have good anti-corrosion retention ability after tightening friction and local mechanical damage.

[0103] Comparative Example 2, which did not undergo APTES interface treatment, had a coating integrity rate that decreased to 77.8%, indicating that the interface construction between zinc flakes and graphene oxide helps improve the stability of the coating during the fastening process.

[0104] The coating integrity rate of Comparative Example 3 after fastening reached 87.0%, which is close to that of the Example, but its red rust area after salt spray reached 8.4%. This result indicates that molybdate intercalation does not simply improve the mechanical wear resistance of the coating, but mainly plays a continuous corrosion inhibition role after local damage caused by fastening.

[0105] Based on the test results above, Examples 1-3 all showed good overall performance in corrosion protection tests including long-term immersion of the complete coating, artificial scratching, scratch salt spray, and repeated tightening.

[0106] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0107] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the claimed invention.

Claims

1. A graphene-synergistic zinc-flake self-healing, long-lasting, fastening, and anti-corrosion composite coating, characterized in that, The composite coating is prepared from the following raw materials in parts by weight: 100 parts of bisphenol A type epoxy resin, 220-320 parts of structured composite modified flake zinc, 45-65 parts of polyamide curing agent, 0.5-1.5 parts of dispersant, 0.3-1.0 parts of thixotropic agent, 0.1-0.3 parts of defoamer, and 35-60 parts of organic solvent; The structured composite modified flake zinc includes graphene oxide modified flake zinc and molybdate-intercalated Mg-Al layered double hydroxide-supported polydopamine-modified hexagonal boron nitride loaded on the surface of the graphene oxide modified flake zinc; the graphene oxide modified flake zinc includes flake zinc treated with 3-aminopropyltriethoxysilane and graphene oxide loaded on the surface of the flake zinc; when preparing the structured composite modified flake zinc, the mass ratio of the molybdate-intercalated Mg-Al layered double hydroxide-supported polydopamine-modified hexagonal boron nitride to the graphene oxide modified flake zinc is 5-12:

100.

2. The graphene-synergistic zinc-flake self-healing long-lasting fastening and anti-corrosion composite coating according to claim 1, characterized in that, The graphene oxide-modified flake zinc is prepared by the following method: 3-aminopropyltriethoxysilane is pre-hydrolyzed in a mixed medium of ethanol and water, and flake zinc is added for surface treatment to obtain aminosilane-modified flake zinc; graphene oxide is pre-dispersed in a mixed medium of ethanol and water, and then the aminosilane-modified flake zinc is added and stirred to composite, so that the graphene oxide is loaded on the surface of the aminosilane-modified flake zinc, and after separation and drying, the graphene oxide-modified flake zinc is obtained.

3. The graphene-synergistic zinc-flake self-healing long-lasting fastening and anti-corrosion composite coating according to claim 2, characterized in that, The median particle size D50 of the zinc flakes is 10–22 μm, and the mass ratio of the zinc flakes, 3-aminopropyltriethoxysilane, and graphene oxide is 100:(0.5–1.5):(0.3–1.0).

4. The graphene-synergistic zinc-flake self-healing long-lasting fastening and anti-corrosion composite coating according to claim 1, characterized in that, The molybdate-intercalated Mg-Al layered double hydroxide supported polydopamine-modified hexagonal boron nitride is prepared by the following method: hexagonal boron nitride is dispersed in tris(hydroxymethyl)aminomethane buffer solution, and dopamine hydrochloride is added for self-polymerization deposition to obtain polydopamine-modified hexagonal boron nitride; the polydopamine-modified hexagonal boron nitride is dispersed in water, and magnesium nitrate hexahydrate and aluminum nitrate nonahydrate are added for co-precipitation and aging to obtain polydopamine-modified hexagonal boron nitride supported on Mg-Al layered double hydroxides; the obtained polydopamine-modified hexagonal boron nitride supported on Mg-Al layered double hydroxides is dispersed in an aqueous solution of sodium molybdate dihydrate for anion exchange to obtain the molybdate-intercalated Mg-Al layered double hydroxide supported polydopamine-modified hexagonal boron nitride.

5. The graphene-synergistic flake zinc self-healing long-lasting fastening and anti-corrosion composite coating according to claim 4, characterized in that, The median particle size D50 of the hexagonal boron nitride is 0.5–5 μm, the mass ratio of the hexagonal boron nitride to dopamine hydrochloride is 100:(5–10), the molar ratio of Mg2+ provided by magnesium nitrate hexahydrate to Al3+ provided by aluminum nitrate nonahydrate is 2.0–3.0:1, and the molar ratio of MoO42- provided by sodium molybdate dihydrate to Al3+ used in the preparation of the Mg-Al layered double hydroxide is 0.75–1.50:

1.

6. The graphene-synergistic flake zinc self-healing long-lasting fastening and anti-corrosion composite coating according to claim 1, characterized in that, The bisphenol A type epoxy resin is E51 epoxy resin, the polyamide curing agent is polyamide 650, the dispersant is a solvent-based polymeric wetting and dispersing agent for epoxy coatings, the thixotropic agent is hydrophilic fumed silica, the defoamer is a polysiloxane defoamer, and the organic solvent is composed of xylene and n-butanol.

7. A method for preparing a graphene-synergistic flake zinc self-healing long-lasting fastening and anti-corrosion composite coating according to any one of claims 1 to 6, characterized in that, Includes the following steps: S1. After pre-hydrolyzing 3-aminopropyltriethoxysilane, surface-treating the zinc flakes is performed. The resulting aminosilane-modified zinc flakes are then stirred and compounded with pre-dispersed graphene oxide to obtain graphene oxide-modified zinc flakes. S2. Hexagonal boron nitride was surface modified with dopamine hydrochloride. Mg-Al layered double hydroxides were formed on the surface of the obtained polydopamine-modified hexagonal boron nitride by co-precipitation of magnesium nitrate hexahydrate and aluminum nitrate nonahydrate. Anion exchange was then performed using an aqueous solution of sodium molybdate dihydrate to obtain molybdate-intercalated Mg-Al layered double hydroxide-supported polydopamine-modified hexagonal boron nitride. S3. The molybdate-intercalated Mg-Al layered double hydroxide supported polydopamine-modified hexagonal boron nitride is added to the dispersion system of graphene oxide-modified flake zinc and stirred for compounding. After separation, washing and drying, the structured composite modified flake zinc is obtained. S4. Pre-disperse the bisphenol A type epoxy resin, organic solvent, dispersant, thixotropic agent and defoamer, then add the structured composite modified flake zinc and mechanically stir to obtain the coating main agent; before use, add polyamide curing agent to the coating main agent and mix evenly to obtain the graphene synergistic flake zinc self-healing long-lasting fastening and anti-corrosion composite coating.

8. The preparation method according to claim 7, characterized in that, In step S1, 3-aminopropyltriethoxysilane is pre-hydrolyzed in a mixed medium of ethanol and water, and graphene oxide is ultrasonically dispersed before being stirred and compounded with the aminosilane-modified zinc flakes. The apparent pH of the system when the aminosilane-modified zinc flakes and graphene oxide are stirred and compounded is 6.5-7.

5. After the aminosilane-modified zinc flakes are added to the graphene oxide dispersion system, they are compounded by mechanical stirring and no further ultrasonic treatment is performed.

9. The preparation method according to claim 7, characterized in that, In step S2, dopamine hydrochloride undergoes self-polymerization deposition in a tris(hydroxymethyl)aminomethane buffer solution with a pH of 8.3–8.7; co-precipitation of Mg-Al layered double hydroxides is carried out under nitrogen protection, and the pH of the co-precipitation system is 9.3–9.5; when anion exchange is performed using an aqueous solution of sodium molybdate dihydrate, the pH of the exchange system is maintained at 7.5–8.5 under nitrogen protection.

10. The preparation method according to claim 7, characterized in that, In step S3, the apparent pH of the system during stirring and compounding is 6.5–7.5.